The use of operations research as a tool for monitoring and managing food-assisted maternal/child health nutrition (MCHN) programs: an example from Haiti - Loechl, Cornelia U.; Ruel, Marie T.; Pelto, Gretel H.; Menon, Purnima (International Food Policy Research Institute, 2005)
This report describes the methods and results of an operations research undertaken to assess the effectiveness of World Vision (WV)'s food assisted maternal and child health and nutrition (MCHN) program in the Central Plateau region of Haiti. The research had three main objectives: (1) to assess the effectiveness of implementation and operations of the program relative to plans; (2) to assess the quality of delivery of the various services; and (3) to explore the perceptions of different stakeholders (i.e., beneficiaries and field implementers) regarding program operations and service delivery and the motivational factors that may affect staff's performance and job satisfaction. The overall goal was to identify constraints to effective operations; it was more important to identify and implement corrective actions that will ensure smooth implementation of the program and its various components. The report is directed to program managers, researchers, and development professionals who are interested in applying operations research methods to evaluate and strengthen similar MCHN programs with a food aid component in developing countries.